Rescuing Newcastle disease virus with tag for screening viral-host interacting proteins based on highly efficient reverse genetics - Wang, Ruiwei; Cao, Xuhong; Lu, Kejia; Chang, Zhengwu; Dong, Xiaoyu; Guo, Hanwei; Wei, Xi; Dang, Ruyi; Wang, Juan; Wang, Xinglong; Xiao, Sa; Liu, Haijin; et al. (Frontiers in Veterinary Science, 2024)
The interaction between viral proteins and host proteins plays a crucial role in the process of virus infecting cells. Tags such as HA, His, and Flag do not interfere with the function of fusion proteins and are commonly used to study protein–protein interactions. Adding these tags to viral proteins will address the challenge of the lack of antibodies for screening host proteins that interact with viral proteins during infection. Obtaining viruses with tagged fusion proteins is crucial. This study established a new reverse genetic system with T7 promoter and three plasmids, which efficiently rescued Newcastle disease virus (NDV) regardless of its ability to replicate in cells. Subsequently, using this system, NDV containing a HA-tagged structural protein and NDV carrying a unique tag on each structural protein were successfully rescued. These tagged viruses replicated normally and exhibited genetic stability. Based on tag antibodies, every NDV structural protein was readily detected and showed correct subcellular localization in infected cells. After infecting cells with NDV carrying HA-tagged M protein, several proteins interacting with the M protein during the infection process were screened using HA tag antibodies. The establishment of this system laid the foundation for comprehensive exploration of the interaction between NDV proteins and host proteins.